Conversion of Waste Tyres into High-Energy Fuel Products Using Pyrolysis Technology - Hyginus Unegbu; Danjuma YAWAS (Universitas Negeri Padang, 2025)
The accumulation of waste tyres poses a critical environmental and public health concern due to their non-biodegradability, complex composition, and fire hazard potential. This study explores the thermochemical valorization of end-of-life tyres into high-energy fuel products through pyrolysis, emphasizing process optimization, product quality assessment, and environmental performance. A fixed-bed pyrolysis system was operated across a temperature range of 350°C to 550°C to evaluate its influence on product distribution and yield characteristics. The maximum oil yield of 52.3% was obtained at 500°C, representing the optimal balance between primary depolymerization and suppression of secondary cracking reactions. The pyrolysis oil exhibited a high heating value (43.6 MJ/kg), suitable for energy applications, but exceeded international standards for sulfur content and viscosity, necessitating upgrading prior to use in transportation fuels. The gaseous fraction, enriched with hydrogen and light hydrocarbons, showed strong potential for process self-sufficiency and co-generation. Solid char demonstrated favorable physicochemical properties for application as a fuel or adsorbent material. Statistical modeling using linear regression accurately predicted oil yield trends, and Aspen Plus® simulations closely aligned with experimental results, validating the process model for scale-up. A comparative life cycle assessment revealed that pyrolysis significantly outperforms incineration in terms of greenhouse gas reduction, energy recovery, and particulate matter emissions. These findings confirm that tyre pyrolysis is a technically feasible and environmentally advantageous approach for sustainable waste management and fuel generation. Further integration with refining technologies and renewable energy inputs is recommended to enhance commercial viability.